Workshop Participants' Perceptions On Student-Sided Learning In Pasuruan District - Labiba, Fatiha Zahra; Abidin, Zainul; Wedi, Agus (Proceedings Series of Educational Studies, 2024)
The workshop is one of the programs that is part of the government's efforts to improve the competence of teachers. Since September 2023, the 1st workshop and 2nd workshop have been held. Then the 3rd workshop will be held in November 2023. The 3rd workshop provides student-friendly learning materials. Therefore, this research was carried out to measure the perceptions of participants who took part in workshop activities. The research method used is descriptive quantitative. The data collection technique uses a questionnaire created using an evaluation model Four-Level Kirkpatrik as a research instrument. The collected data was then processed using descriptive statistical techniques using SPSS. The research results showed that the majority of participants gave positive perceptions of reactions. However, some participants with a percentage of 12.6% were less suited to the application of learning models, learning methods and learning media. These findings provide insight for the organizers in order to improve a